Direitos sociais, orçamento público e escassez de recursos públicos financeiros do estado - Cabral, Denise Maciel de Albuquerque (2016)
This study aims to investigate the relationship between social rights guaranteed in the Federal Constitution of 1988, the public budget and the scarcity of financial resources of the State. It starts with the premise that the State's financial resources are scarce and are not sufficient to meet all demands. Then the need to choose in which areas these funds will be used arises. Because of the extensive list of social rights brought by the Constitution, the question of budget choices becomes relevant, requiring the search criteria that can guide the public administrator. The research methodology used was bibliographical and documentary research, with analysis of jurisprudence on the subject. Results revealed that Legislative and Executive Powers have no arguments to justify the allocative choices budget, treated as a simple income and expenses document, stage of political disputes in which the personal interest of political prevails over the public needs. On the contrary, the Judiciary, trying to fill an institutional deficiency, has used an increasingly activist positioning, determining financial contributions to the solution of individual specific cases. That conduct has unbalanced state budgets, committing significant part of them to the judgments attendance. As a conclusion, although it’s not possible to use a single criterion of orientation, is necessary to find a balance between public authorities responsible for the allocative decisions of financial resources, Legislative and Executive, which are responsible for presenting appropriate and consistent justifications to public needs, and the Judiciary, responsible for controlling the legality and constitutionality of these choices, in order to avoid an exaggerated activism and undue interference in the public budget. That way, it can be possible to start a serious movement of realization of social rights guaranteed in the Constitution.